2017
DOI: 10.3389/fnsyn.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

APP Deletion Accounts for Age-Dependent Changes in the Bioenergetic Metabolism and in Hyperphosphorylated CaMKII at Stimulated Hippocampal Presynaptic Active Zones

Abstract: Synaptic release sites are characterized by exocytosis-competent synaptic vesicles tightly anchored to the presynaptic active zone (PAZ) whose proteome orchestrates the fast signaling events involved in synaptic vesicle cycle and plasticity. Allocation of the amyloid precursor protein (APP) to the PAZ proteome implicated a functional impact of APP in neuronal communication. In this study, we combined state-of-the-art proteomics, electrophysiology and bioinformatics to address protein abundance and functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Giulietti et al 45 found k f reductions in the hippocampus, temporal lobe, posterior cingulate and parietal cortex in LOAD and proposed that these changes may reflect reductions in metabolic mitochondrial activity 89 . As agerelated reductions of hippocampal metabolic activity have also been observed in animal studies 90,91 , the decline in hippocampal k f observed here may reflect reduced metabolic activity related to aging. Age-related damage to mitochondria of microglia has also been linked to sustained microglia neuroinflammation 92 .…”
Section: Discussionsupporting
confidence: 76%
“…Giulietti et al 45 found k f reductions in the hippocampus, temporal lobe, posterior cingulate and parietal cortex in LOAD and proposed that these changes may reflect reductions in metabolic mitochondrial activity 89 . As agerelated reductions of hippocampal metabolic activity have also been observed in animal studies 90,91 , the decline in hippocampal k f observed here may reflect reduced metabolic activity related to aging. Age-related damage to mitochondria of microglia has also been linked to sustained microglia neuroinflammation 92 .…”
Section: Discussionsupporting
confidence: 76%
“…DE particles, a primary component of TRAP, have also been reported to activate microglia both in vitro and in vivo [ 6 , 89 91 ]. Further, developmental exposure to DE particles has been shown to increase inflammatory cytokines and alter microglia morphology in a toll-like receptor 4 (TLR4) dependent manner [ 31 ]. TLR4 has been shown to play a critical role in the maternal immune activation mouse model of autism, in which prenatal infection-induced activation of TLR4, and subsequent elevation of the key inflammatory cytokines IL6 and IL17α, are responsible for autistic-like behavior observed in pups [ 12 , 91 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, hippocampal seizures, depression, and persistent cognitive effects were found when ethanol exposure occurred during this peak period of brain growth [ 29 , 30 ]. On a related note, air pollution exposure has been shown to cause a decrease in cortical thickness and lateral ventricular size in rodent models [ 10 , 31 ], suggesting that this period of intense brain growth in the third trimester may be an important window of vulnerability for neurodevelopmental toxicity related to TRAP as well. In rodents, this window of particularly robust brain growth extends into the postnatal period [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…LTP can also occur following pairing of low-frequency presynaptic stimulation with postsynaptic depolarization ( Campanac & Debanne, 2008 ; Andrade-Talavera et al, 2016 ). LTP resulting from paired stimulation is one type of spike timing-dependent plasticity (STDP) in which the temporal order of spiking determines the type of plasticity induced; if presynaptic spiking occurs prior and close in time to postsynaptic spiking, then LTP occurs, while the reverse order (post →pre) produces long-term depression (LTD) ( Bi & Poo, 1998 ; Campanac & Debanne, 2008 ; Andrade-Talavera et al, 2016 ) (for reviews on STDP see Edelmann, Cepeda-Prado & Leßmann, 2017 ; Caporale & Dan, 2008 ; Dan & Poo, 2004 ). Postsynaptic stimulation can come in the form of a single spike or a burst of APs, and the relative ability of these two stimuli to induce LTP changes with age.…”
Section: Responses To Synaptic Stimulationmentioning
confidence: 99%